IMPLEMENTASI PROGRAM PENGEMBANGAN SISTEM PENDUKUNG BAGI USAHA MIKRO, KECIL DAN MENENGAH: Studi Kasus di Kabupaten Karawang - Wulan, Windu; Atthahara, Haura; Azizah, Ani Nurdiani; Harmiati, Harmiati; Mulyadi, Mulyadi (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2022)
One of government’s efforts to overcome poverty is to develop the Micro, Small and Medium Enterprises (MSME) sector. In developing MSME sector the central government and local governments carry out a support system development program for MSMEs. One of them is Department of Cooperatives and SMEs Karawang Regency. However in practice, MSMEs in Karawang Regency have difficulties in developing their products, one of which is the lack of public interest in MSME products. The purpose of this study was to find out how to implement support system development program for MSMEs at the Department of Cppperatives and SMEs Karawang Regency by using the implementation indicators form Quade (Akib, 2010) namely 1) the disered policy, 2) the target group, 3) implementing organization, 4) environmental factors. The research methodology used in this research is descriptive qualitative. The results of the discussion of this study are the Office of Cooperatives and Small and Medium Enterprises (SME) of Karawang Regency has implemented a support system depelovment program for MSMEs well, such as MSME actors in the promotion and marketing of their products through events or good activities organized by the local government. As well as other local governments as well as through cooperation carried out by private parties such as hotels modern shopping center or malls. However, in this implementation it is still influenced by environmental factors such as low public interest in MSME products.